2014
DOI: 10.1177/1087054714533192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Activity Intervention on Motor Proficiency and Physical Fitness in Children With ADHD: An Exploratory Study

Abstract: Children with ADHD exhibit low levels of motor proficiency and cardiovascular fitness; thus, using the combined 12-week SDHRP and fitness training positively affected children with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 27 publications
4
60
0
6
Order By: Relevance
“…Hence, preliminary evidence suggests that when PA groups are compared to active comparison groups, group x time effect sizes on symptom severity are small or near-zero, but when they are compared to no-intervention control groups they are often moderate-large. This hypothesis is also supported by the broad array of PA program formats demonstrating promise, traditional physical education games (Bustamante et al, 2016), distance running (Wendt, 2000), video games (Benzing & Schmidt, 2017), table tennis (Pan et al, 2016), mechanical horseback riding (Pan et al, 2017), swimming (Verret, Guay, Berthiaume, Gardiner, & Béliveau, 2012), sports therapy , yoga (Chou & Huang, 2017), and interactive cycling (Bowling et al, 2017), among others. If it is the case that the features of PA programs that are most important to improving behavior of children with ADHD are those associated with the environments in which the PA is taking place, this may reasonably be interpreted as a rationale for intentionally tailoring these factors to optimize impact.…”
Section: Evidence From Observational Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Hence, preliminary evidence suggests that when PA groups are compared to active comparison groups, group x time effect sizes on symptom severity are small or near-zero, but when they are compared to no-intervention control groups they are often moderate-large. This hypothesis is also supported by the broad array of PA program formats demonstrating promise, traditional physical education games (Bustamante et al, 2016), distance running (Wendt, 2000), video games (Benzing & Schmidt, 2017), table tennis (Pan et al, 2016), mechanical horseback riding (Pan et al, 2017), swimming (Verret, Guay, Berthiaume, Gardiner, & Béliveau, 2012), sports therapy , yoga (Chou & Huang, 2017), and interactive cycling (Bowling et al, 2017), among others. If it is the case that the features of PA programs that are most important to improving behavior of children with ADHD are those associated with the environments in which the PA is taking place, this may reasonably be interpreted as a rationale for intentionally tailoring these factors to optimize impact.…”
Section: Evidence From Observational Studiesmentioning
confidence: 94%
“…Smaller studies have yielded equivocal results, but none suggest a physical fitness advantage for children with ADHD. A study of Taiwanese children (N=36, 7-14 year-old) found that those with ADHD completed 20 laps on the 20-meter PACER compared to 22 laps among TD peers (Pan et al, 2017). In a trial with African-American children with ADHD and/or Disruptive Behavior Disorders (N=35, 6-12 years-old), half of children were categorized by FitnessGram as "Needs Improvement" while the other half were categorized as "Needs Improvement -Health Risk" (Bustamante et al, 2016).…”
Section: Studies In Middle-late Childhood (Ages 7-12)mentioning
confidence: 99%
“…Estudios con menos participantes presentaron resultados contradictorios, pero ninguno sugiere ventajas en los niveles de aptitud física para los niños con TDAH. Un estudio con niños y niñas taiwaneses (N = 36, entre 7 a 14 años) encontró que los niños con el TDAH completaron 20 vueltas en el PACER comparado con los niños aparentemente saludables, los cuales completaron 22 vueltas (Pan et al, 2017). Un estudio de intervención en niños y niñas afroamericanos con TDAH o con trastorno de conducta disruptiva (N = 35, entre 6 a 12 años), evidenció que la mitad de los niños fueron clasificados por FitnessGram como "necesita mejorar" mientras que la otra mitad fue clasificada como "necesita mejorar-riesgo a la salud" (Bustamante et al, 2016).…”
Section: Estudios Durante La Niñez Temprana (4-6 Años)unclassified
“…Sin embargo, cuando el grupo que recibió AF es comparado con un grupo que no recibió AF, los tamaños de efecto son de moderados a grandes. Esta hipótesis también está sustentada por la variedad de formas en que se ofrece la AF, las cuales incluyen formato tradicional de la clase de educación física (Bustamante et al, 2016), correr distancias largas (Wendt, 2000), AF a través de video juegos (Benzing & Schmidt, 2017), tenis de mesa (Pan et al, 2016), equitación (Pan et al, 2017), natación (Verret, Guay, Berthiaume, Gardiner, & Béliveau, 2012), AF junto con psicología (Choi et al, 2015), yoga (Chou & Huang, 2017) y ciclismo virtual (Bowling et al, 2017, entre otros. De ser cierto que las características más importantes de los programas de AF para mejorar el comportamiento de niñosy niñas con TDAH son aquellas asociadas con el ambiente en el cual se ofrece la AF, entonces sería razonable adaptar los programas de AF de forma tal que incluyan los factores ambientales adecuados para poder optimizar los beneficios del programa.…”
Section: Evidencia De Estudios De Intervenciones De Varias Semanasunclassified
“…A recent systematic review11) of 14 EAA/T studies have validated psychotherapeutic effectiveness that significant biopsychosocial outcomes have been achieved, such as decreased negative affect, improvement of adaptive functioning, and perceived wellness. In addition, a randomized controlled trial demonstrated that children with autism spectrum disorder who received 10-week therapeutic horseback riding showed not only significant improvement in social cognition, communication and expressive language but also irritability and hyperactivity behaviors compared to barn activity control groups 12). Application of EAA/T on ADHD subjects have been in the beginning stage and a very few studies addressed these issues.…”
Section: Introductionmentioning
confidence: 99%